107. Impact of Switching to an Antiretroviral Regimen Containing Tenofovir Alafenamide on Weight Gain and Development of Metabolic Side Effects. (31st December 2020) - Darnell, Julia; Karris, Maile; Qin, Huifang; Hill, Lucas
Abstract: Background: Tenofovir is a common backbone of many antiretroviral (ARV) regimens for the treatment of HIV. Although limited, data has shown that tenofovir alafenamide (TAF) may contribute to weight gain. Our study evaluated the impact on weight gain and metabolic effects of people living with HIV (PLWH) who were switched to ARV regimens containing TAF in the real-world setting. Methods: Single center retrospective cohort study. Included were PLWH who were on an ARV regimen not containing TAF, who were switched to a TAF containing regimen between January 1, 2016 and September 30, 2018. The control group contained patients on a TAF free ARV regimen throughout the study period. The primary outcome was change in weight from baseline at 12 months post switch. Secondary outcomes were change in BMI, development of new diabetes, hypertension, and/or hypercholesteremia. Results: A total of 446 patients were switched to a TAF containing regimen during the study period, and included as cases. Controls (n=162) consisted of patients who continued a regimen containing abacavir/lamivudine/dolutegravir during the study period. The control group was older (54 vs. 49 years, p< 0.0001), had a higher proportion of black patients (17.9% vs 11.4%, p=0.04), had a higher mean VACS score (27 vs 18, p< 0.0001), and had fewer patients with reported physical activity (21.6% vs 30%, p=0.04), although this was driven by a higher proportion of patients in the controls with unknown physical activity. Cases showed significantly more weight gain compared to controls at 12 months (2.01kg vs 0.77kg, p=0.001). There was a higher percentage of increase in BMI class in the cases compared to control at 12 months (18.2% vs 9.9%, p=0.01). Increase in weight at 12 months varied dependent on the rest of the antiretroviral regimen (Table 1). Cases had a significant increase in the number of patients with hypertension (35.9% pre vs 43.7% post, p=0.02) and hyperlipidemia after the switch (7.8% pre and 18.4% post, p< 0.00001), while controls only had a significant increase in hyperlipidemia (50.0% pre vs 67.9% post, p=0.01). Conclusion: Patients switched to an ARV regimen containing TAF gained significantly more weight, and had higher rates of increase in BMI category than those who stayed on a non TAF containing regimen throughout the study period. Disclosures: All Authors : No reported disclosures